4-Degree-of-freedom anti-windup scheme for plants with actuator saturation. (November 2016) - Li, Zhong-Shen; Mo, Xiao-Qin; Guo, Shang-Jia; Lan, Wei-Yao; Huang, Chun-Qing
Highlights: A 4-Degree-of-Freedom anti-windup scheme based on transfer function description is developed for anti-windup compensation. The set-point response is decoupled from the disturbance response, while both of them can be specified arbitrarily. The effect of actuator saturation is almost eliminated when the controllers are suitably selected. It provides a fairly straightforward tuning rule in frequency domain instead of LMIs in many modern anti-windup techniques that suffers an infeasibility problem. Numerical example shows remarkable performance improvement of the proposed scheme in comparison with IMC-based, low-order or dynamic compensation anti-windup schemes. Abstract: In this paper, a 4-degree-of-freedom (DoF) anti-windup scheme is developed for anti-windup compensation of plants with actuator saturation. Instead of LMIs (Linear Matrix Inequalities) in modern anti-windup technique, sufficient stability conditions of the proposed anti-windup scheme are derived under the framework of IQC (Integral Quadratic Constraint). The sufficient conditions are formulated as a checking on the positive definiteness of the related transfer function at all frequencies for MIMO systems (or positive sign for SISO systems), which provides a fairly straightforward tuning rule in the frequency domain. Moreover, by virtue of the proposed scheme, control design for disturbance response is decoupled from set-point response. The proposed scheme can be implemented without system states or state estimates. Compared with IMC-based, low-order or dynamic compensation anti-windup schemes, numerical example shows remarkable performance improvement of the proposed scheme for the saturated systems.